Enhancing Global Diversity and Cultural Literacy Through DILAN Model with Kamasan Painting - Sudiartini, Ni Pande Kadek Dewi; Kertih, I Wayan; Suastika, I Nengah (Journal of Innovation in Educational and Cultural Research, 2026)
This study develops the DILAN (Dalami/Explore, Informasikan/Inform, Latihkan/Practice, Amati/Observe, Nilai/Assess) learning model assisted by Wayang Kamasan Painting to improve global diversity character and cultural literacy in elementary students. The research is based on the limited use of local wisdom in social studies, which makes learning tend to emphasize memorization. Using a Research and Development (RD) design with the ADDIE model, the study followed five stages: analysis, design, development, implementation, and evaluation. Research instruments included expert validation questionnaires, observation sheets, student and teacher response questionnaires, and cultural literacy tests. The design test showed a feasibility level of 95% (very good). Validation by content, design, and media experts scored ?90% (very good). Student practicality trials reached 87–92.3% (good to very good), while teacher assessment was 93.8% (very good). Effectiveness testing showed significant results: global diversity (t = 2.104 2.064) and cultural literacy (t = 2.121 2.064), indicating H1 was accepted. Thus, the DILAN model with Wayang Kamasan assistance is valid, practical, and effective. It serves as an innovative learning model that integrates local culture, supports character formation, and strengthens national identity in the globalization era.